Exploring Environmental Performance and the Impact of Environmental Disclosure on Market Performance: A Literature Review - Febi Saputra (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the intricate relationship between a company's Environmental Performance (EP), Environmental Disclosure (ED), and Market Performance (MP). T To investigate these dynamics, the research employs a literature review methodology, focusing on publications in the Sinta database over the last five years. The inclusion criteria ensure relevance to the relationship between environmental performance, environmental disclosure, and market performance in the Indonesian mining sector. The study aims to deepen our understanding of these variables' interactions, providing valuable contributions to academic and practical knowledge in this field. The findings underscore the crucial link between sustainable practices, transparent communication, and positive market dynamics. Companies with robust environmental performance and effective disclosure not only contribute to sustainability but also gain increased market acceptance and trust. The research suggests avenues for future exploration, including nuanced factors influencing these relationships and the incorporation of moderation variables. Ultimately, this study emphasizes the importance of environmental initiatives and transparent communication for long-term financial success in the mining sector